Role and mechanism of nitric oxide-regulated cGAS/STING pathway-mediated inflammatory response in hypoglycemia-induced coronary artery endothelial cell injury - Wenping Luo; Xiao Wei; Qian Xiao (PLoS ONE, 2026)
Background Hypoglycemia in diabetes markedly increases the risk of coronary artery events, but the mechanism by which it damages vascular endothelium through nitric oxide (NO) regulation of innate immune pathways remains unclear. Objective This study aimed to investigate the mechanism by which NO may induce vascular endothelial injury under hypoglycemic conditions, potentially through activation of the cyclic GMP-AMP synthase/stimulator of interferon genes (cGAS/STING) pathway. Methods The mouse model of diabetic hypoglycemia and a primary endothelial cell model of low-high glucose cycling were constructed. Gene knockout, molecular biology, and functional assay were adopted. Results In the hypoglycemia group, endothelial cell NO levels increased by 4.1 times, while mitochondrial oxygen consumption rate (OCR) and ATP production decreased by 48.2% and 53.6%, respectively ( P < 0.01), and inducible Nitric Oxide Synthase (iNOS) inhibitors could reverse the damage. Hypoglycemia induced a 5.9-fold increase in mitochondrial DNA (mtDNA) release, accompanied by a 3.8-4.2-fold upregulation in cGAS/STING protein expression ( P < 0.01), suggesting that NO may contribute to the upregulation of the cGAS/STING pathway indirectly by promoting mtDNA release. STING knockout blocked pathway activation but did not affect mtDNA release. In the hypoglycemia group, IL-6 and TNF-α levels increased by 7.8 times and 7.6 times, respectively, cardiomyocyte survival rate dropped to 62.5%, and left ventricular function decreased by 35.3% ( P < 0.01), all of which could be improved by STING inhibitors. Inhibition of iNOS or STING markedly restored mitochondrial function or suppressed inflammation, respectively, and combined intervention restored cardiomyocyte survival rate to 91.2% ( P < 0.01). Conclusion Hypoglycemia induces mitochondrial damage and mtDNA release via the iNOS-NO axis, which may subsequently promote the activation of the cGAS/STING pathway, leading to vascular and myocardial inflammatory injury. Inhibition of iNOS or STING can mitigate the damage, revealing the “NO-cGAS/STING-inflammation axis” as a core mechanism and potential therapeutic target.